Digitoxose as powerful glycosyls for building multifarious glycoconjugates of natural products and un-natural products - Kemeng Li; Zhengyan Guo; Liping Bai (Synthetic and Systems Biotechnology)
Digitoxose, a significant 2,6-dideoxyhexose found in nature, exists in many small-molecule natural products. These digitoxose-containing natural products can be divided into steroids, macrolides, macrolactams, anthracyclines, quinones, enediynes, acyclic polyene, indoles and oligosaccharides, that exhibit antibacterial, anti-viral, antiarrhythmic, and antitumor activities respectively. As most of digitoxose-containing natural products for clinical application or preclinical tests, this review also summarizes the biosynthesis of digitoxose, and application of compound diversification by introducing sugar plasmids. It may provide a practical approach to expanding the diversity of digitoxose-containing products.